Performance enhancement of normally off InAlN/AlN/GaN HEMT using aluminium gallium nitride back barrier. (March 2022) - Chand, Nisarga; Adak, Sarosij; Swain, S.K.; Biswal, Sudhansu Mohan; Sarkar, A.
Highlights: DC and SCEs performances are investigated for enhancement-mode HEMT with variation of AlGaN back barrier thickness. 2D Sentaurus TCAD hydrodynamic simulation model are calibrated with experimental results. Threshold voltage is increased and gate leakage current reduced. AlGaN back barrier device featured better electrostatic control and significant improvement in short channel effects. Abstract: In the present work, we have studied the influence of Aluminium Gallium Nitride (AlGaN) back-barrier (BB) thickness on the direct current (DC) and short channel effects (SCEs) of lattice matched In0.17 Al0.83 N/AlN/GaN Gate-Recessed normally off high electron mobility transistor (HEMT) grown on silicon carbide substrate. The extensive simulations are done by the 2Dimenssional synopsis TCAD by means of Hydrodynamic (HD) mobility model and calibrated with the experimental result. The DC performance of the device has been studied using the simulations for different BB thickness (tbb ) and a comparison was made with regard to the device without BB for gate length (Lg) 50 nm and 75 nm. The result indicates that use of AlGaN BB has several advantages like improving the SCEs, reducing leakage current and resulting higher threshold voltage (Vth ). Therefore the implementation of AlGaN BB in related devices perhaps another way out for high power and digital switching purpose. Graphical abstract: Image, graphical abstract